Analisis Faktor yang Berhubungan dengan Kualitas Hidup pada Orang dengan Skizofrenia - Handayani, Desy; Rahayuningsih, Atih; Basmanelly, Basmanelly (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This study aims to analyze factors related to quality of life in ODS. The research method uses a quantitative approach with a cross-sectional design. The study results show a significant relationship between family support, self-stigma, self-esteem, work, and physical health with the quality of life of ODS (p-value: 0.000). Family support is The factor most related to the quality of life (0.985). In conclusion, there is a relationship between the quality of life of ODS and family support, self-stigma, self-esteem, physical health, and work, with the dominant factor influencing the quality of life of ODS being the family support factor. Keywords: Quality of Life, Schizophrenia